Hemodynamic Relevance of Anomalous Coronary Arteries Originating From the Opposite Sinus of Valsalva-In Search of the Evidence - Bigler, Marius Reto; Ashraf, Afreed; Seiler, Christian; Praz, Fabien; Ueki, Yasushi; Windecker, Stephan; Kadner, Alexander; Räber, Lorenz; Gräni, Christoph (Frontiers in Cardiovascular Medicine, 2021)
Coronary artery anomalies (CAA) represent a heterogeneous group of congenital disorders of the arterial coronary circulation, defined by an anomalous origin of the coronary ostium and/or vessel course. Of particular interest are anomalous coronary arteries originating from the opposite sinus of Valsalva (ACAOS). The interarterial variants (with the anomalous vessel situated between the great arteries) are historically called “malignant”, based on an anticipated higher risk for myocardial ischemia and sudden cardiac death (SCD), especially affecting young patients during strenuous physical activity. However, the interarterial course itself may not be the predominant cause of ischemia, but rather represents a surrogate for other ischemia-associated anatomical high-risk features. As the exact pathophysiology of ACAOS is not well understood, there is a lack of evidence-based guidelines addressing optimal diagnostic work-up, downstream testing, sports counselling, and therapeutic options in patients with ACAOS. Therefore, treating physicians are often left with uncertainty regarding the clinical management of affected patients. This review focuses on the pathophysiologic consequences of ACAOS on myocardial ischemia and discusses the concept of the interplay between fixed and dynamic coronary stenosis. Further, we discuss the advantages and limitations of the different diagnostic modalities and give an outlook by highlighting the gaps of knowledge in the assessment of such anomalies.